THE TECHNIQUES SEPARATING THREE OVERLAP PEAKS IN GAMMA SPECTRUM - Trịnh Ngọc Pháp; Mai Xuân Trung (Tạp chí Khoa học Đại học Đà Lạt)
Separating the three overlapped peaks of a Gamma spectrum is essential requirements in experimental nuclear physics as well as in analysis of gamma-ray spectrum. In this paper, we present the results of calculations for the problem of overlap peaks, in which three individual peaks are overlapped with each other. The calculation procedure was performed by the Levenberg-Marquardt algorithm with linear and nonlinear background. Based on separating the two overlap peaks method has been implemented in our previous article, the separating three overlap peaks was successfully implemented in this paper, in which the calculations were tested with gamma-ray spectra by using a Semiconductor detector and a Scintillator detector.